Dakwah Akhir Zaman Ustadz Zulkifli Muhammad pada Kanal UZMA Media TV - Siti Rohimah; M. Saripuddin; Adi Iqbal; Zulqarnin; Muhsin Ruslan (MAUIZOH: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
This research is motivated by a review by M Ilham Yunihandoko about the apocalypse, in his review it only describes the general picture. Second, the writings of Ustadz Abu Nida' Chomsaha Shofwan, a salafi cleric who lives in Yogyakarta and actively preaches on Youtube. His writings published in online articles stated that the issue of the signs of the apocalypse was deliberately raised, to remind us, because most people have forgotten about it. Third, is the Muslim Hadith, namely the news brought by the angel Gabriel about the signs of the apocalypse. This study aims to determine the truth of Ustadz Zulkifli Muhammad Ali's lecture about the end of time. This research is a library research or library research that is qualitative descriptive exploratory, qualitative because the research deals with data not numbers, descriptive because it collects and analyzes narrative data. The research was conducted on the youtube channel "UZMA Media TV Channel" with literary data collection techniques, namely digging library materials that are in line with the object of study.